Adolescent Voices and Perspectives on Food and Nutrition: Feasibility of an Innovative Participatory Methodology. (7th June 2021) - Fleming, Catharine; De Oliveira, Juliano Diniz; Schmied, Virginia; La, la Girish; Sharma, Deepika; Koniz-Booher, Peggy; Pérez-Escamilla, Rafael; Third, Amanda
Abstract: Objectives: Adolescence presents a window of opportunity for establishing lifelong dietary habits that support nutritional well-being today and for future generations. The aim of this study was to explore an innovative highly participatory qualitative methodology to capture adolescents' food and nutrition perspectives and lived experiences. Adolescence presents a window of opportunity for establishing lifelong dietary habits that support nutritional well-being today and for future generations. The aim of this study was to explore an innovative highly participatory qualitative methodology to capture adolescents' food and nutrition perspectives and lived experiences. Methods: Adolescents' experiences of food and nutrition were collected through a distributed data gathering approach, based on a process in which participants completed creative participatory workshop-based qualitative activities that explored the participants' lived experiences. This methodology allowed for adaptation and administration of the study across 18 countries. The workshop manual included diverse participatory activities to collect food and nutrition information on dietary intake, body image, influences on food choices, food environments, barriers to healthy eating, and solutions voiced by adolescents. All workshop data were digitised and uploaded to a secure online repository for analysis by researchers. Qualitative thematic coding and quantitative dietary analyses based on the NOVA classification system were used for analysis. After each workshop, facilitators completed a short open-ended questionnaire to provide feedback on workshop activities. Results: Thirty-seven workshops were successfully completed with 656 adolescents across 18 countries and 5 world regions. Workshops included a diverse sample of adolescents, together with highly vulnerable groups such as displaced refugees in Sudan. The application of a distributed data gathering methodology was found to effectively engage adolescents in openly discussing their own food and nutrition experiences. Conclusions: The highly innovative distribute data methodological approach allowed adolescent to express their food and nutrition needs and wants, which is key for better understanding of diverse perspectives and experiences to improving policies and programs. Funding Sources: UNICEF.